The Impossible Dream: The Early Years of The College of The Bahamas - Brown, Roger G. (International Journal of Bahamian Studies, 2014)
Remarks by Dr. Roger G. Brown, former Registrar of The College of The Bahamas, Coordinator, Bahamas General Insurance Association, given at the official opening of the Harry C. Moore Library and Information Centre of The College of The Bahamas on April 8, 2011.